Determinants of private commercial banks profitability in Ethiopia: Empirical evidence - Negash, Tekalign (YAYASAN MITRA PERSADA NUSANTARA, 2023)
The major objective of the study was to examine factors that determined private commercial bank profitability in Ethiopia by using panel data of thirteen private commercial banks from year 2010 to 2021. The study used random effect multiple linear regressions models to investigate factors that determine the profitability of private commercial banks. To obtain information relevant to the study, secondary data especially annual audited financial statement of banks was used. Besides, in the study only thirteen private commercial banks purposively selected sample from this population due to the availability of 12 years’ data. The findings of the study reveals that management efficiency and loan to deposit ratio have statistically significant and positive relationship with banks’ profitability. On the other hand, variables like liquidity have a negative and statistically significant relationship with banks’ profitability. Conversely, the relationship for funding cost, gross domestic product and inflation rate is found to be positive and statistically insignificant. Therefore, it is recommended that private commercial banks should increase the statutory minimum reserves of capital which a bank or other financial institution must have available (capital adequacy), diversify their types of deposits, increase their size by increasing the number of branches and network